A standard framework for assessing the costs and benefits of restoration: introducing The Economics of Ecosystem Restoration. Issue 3 (28th October 2021) - Bodin, Blaise; Garavaglia, Valentina; Pingault, Nathanaël; Ding, Helen; Wilson, Sarah; Meybeck, Alexandre; Gitz, Vincent; d'Andrea, Sara; Besacier, Christophe
Abstract : While the policy momentum behind ecosystem restoration has never been stronger, restoration finance remains insufficient. A crucial information gap to unlock finance is the lack of robust and consistent data on the costs and benefits of restoration. This is due in part to the wide variety of contexts, interventions, and objectives of restoration projects, and to the absence of well‐defined standards and protocols for cost and benefit data collection. To fill this gap, we developed a standard framework to assess the costs and benefits of restoration projects and specific restoration interventions. The associated template for data collection, which was tested for usability during a piloting phase, is the first output of The Economics of Ecosystem Restoration (TEER), a multi‐partner initiative under the aegis of the UN Decade on Ecosystem Restoration. It is the first attempt ever to improve the robustness and comparability of data on the economics of ecosystem restoration collected from the field at a global scale. Widespread adoption of this framework and associated template by a wide range of organizations implementing or financing restoration would allow for standardized data to be fed into a jointly owned database of restoration costs and benefits and serve as a basis for the further investigation of the economics of ecosystem restoration, including cost‐benefits analysis. Better information on costs and benefits will help to inform accurate budgeting access to finance for restoration projects, and make them more likely to achieve their set goals and desired quantitative outcomes (e.g. area restored).